Did evolution create a flexible ligand-binding cavity in the urokinase receptor through deletion of a plesiotypic disulfide bond? - Leth, Julie M. (J Biol Chem, 2019)
The urokinase receptor (uPAR) is a founding member of a small protein family with multiple Ly6/uPAR (LU) domains. The motif defining these LU domains contains five plesiotypic disulfide bonds stabilizing its prototypical three-fingered fold having three protruding loops. Notwithstanding the detailed knowledge on structure-function relationships in uPAR, one puzzling enigma remains unexplored. Why does the first LU domain in uPAR (DI) lack one of its consensus disulfide bonds, when the absence of this particular disulfide bond impairs the correct folding of other single LU domain-containing proteins? Here, using a variety of contemporary biophysical methods, we found that reintroducing the two missing half-cystines in uPAR DI caused the spontaneous formation of the corresponding consensus 7–8 LU domain disulfide bond. Importantly, constraints due to this cross-link impaired (i) the binding of uPAR to its primary ligand urokinase and (ii) the flexible interdomain assembly of the three LU domains in uPAR. We conclude that the evolutionary deletion of this particular disulfide bond in uPAR DI may have enabled the assembly of a high-affinity urokinase-binding cavity involving all three LU domains in uPAR. Of note, an analogous neofunctionalization occurred in snake venom α-neurotoxins upon loss of another pair of the plesiotypic LU domain half-cystines. In summary, elimination of the 7–8 consensus disulfide bond in the first LU domain of uPAR did have significant functional and structural consequences.